Does Chemotherapy Induce Autolytic Debridement in Cancer Wounds?: A Case Study - Anam, Khoirul; Yusuf, Saldy (Basic and Applied Nursing Research Journal, 2024)
Cancer wounds are complex wounds with various challenges, and one of essential interventions used is chemotherapy. However, the clin-ical effects of chemotherapy on the status of cancer wounds have not been extensively reviewed, raising the question of whether it has bene-ficial or detrimental effects. The study wanted to identify whether chemotherapy can induce autolytic debridement. A prospective case study involved a patient who underwent four treatment sessions in a regional hospital in eastern Indonesia. Wound assessment was per-formed using the Bates-Jensen Wound Assessment Tool (BWAT). In the first wound treatment, the BWAT score was 38; by the fourth treat-ment, the score increased to 45, suggesting a worsening of the wound status. However, this anomaly is positive for the wound status, as au-tolysis occurred in the slough and necrotic tissue resulting from the chemotherapy.This case study illustrates the positive effect of chemo-therapy on necrotic and slough tissue by inducing autolytic debride-ment.